The challenges of the teacher in the university of the 21st century: Dealing with digital competence and student engagement - Abanades Sánchez, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
For a long time, the teacher has been subject not only to an ad hoc learning of digital skills but also to prepare to develop skills in their students in the different modalities: face-to-face, online, hybrid. This chapter exposes some challenges for the teacher, as well as the relationship of connectivism as a form of learning. The self-perception of the students of various courses about the know-how of the teacher in virtual classes will be exposed. As main conclusions, greater management by the teacher in digital competence is necessary, as well as the management of strategies to dynamize the sessions.